Structure–Function Analysis of Interallelic Complementation in ROOTY Transheterozygotes. Issue 3 (29th April 2020) - Brumos, Javier; Bobay, Benjamin G.; Clark, Cierra A.; Alonso, Jose M.; Stepanova, Anna N.
Abstract : Structure–function modeling explores the basis of interallelic complementation in multiple combinations of rooty alleles. Abstract: Auxin is a crucial plant growth regulator. Forward genetic screens for auxin-related mutants have led to the identification of key genes involved in auxin biosynthesis, transport, and signaling. Loss-of-function mutations in genes involved in glucosinolate biosynthesis, a metabolically related route that produces defense compounds, result in auxin overproduction. We identified an allelic series of fertile, hypomorphic Arabidopsis ( Arabidopsis thaliana ) mutants for the essential glucosinolate biosynthetic gene ROOTY ( RTY ) that exhibit a range of phenotypic defects characteristic of enhanced auxin production. Genetic characterization of these lines uncovered phenotypic suppression by cyp79b2 cyp79b3, wei2, and wei7 mutations and revealed the phenomenon of interallelic complementation in several RTY transheterozygotes. Structural modeling of RTY elucidated the relationships between structure and function in the RTY homo- and heterodimers, and unveiled the likely structural basis of interallelic complementation. This work underscores the importance of employing true null mutants in genetic complementation studies.